A Fixed Point Theorem for a Pair of Generalized Nonexpansive Mappings in Uniformly Convex Metric Spaces (Journal of Mathematical Study, 2022)
In uniformly convex metric spaces, we study the existence and uniqueness of a common fixed point for a pair of generalized nonexpansive mappings with some weak conditions. Meanwhile, we introduce a new Krasnoselskii type iterative algorithm for approximating the common fixed point. A numerical example is also given to demonstrate the main result. Our results generalize and improve some recent corresponding results.